Comparison of Microbiological and Physicochemical Quality of Tap and Dispenser Water from Different Mid-Range Restaurants of Dhaka City, Bangladesh - Alam, Nur; Jamal, Rubayat; Alam, SM Sabbir; Moniruzzaman, Mohammad (Bangladesh Journal of Microbiology, 2016)
Dhaka is the most populous city in Bangladesh and the tenth-largest metropolitan in the world with about twelve million inhabitants. Most people of Dhaka have low or middle ranged incomes and frequently use roadside mid range restaurants to take their meals and drinking water. Water quality is a significant health concern in Bangladesh and is a probable source of many water borne diseases and outbreaks. Tap water and dispenser water samples were collected from ten roadside restaurants. These samples were analyzed for pH, salinity, conductivity, TDS (total dissolved solid) for physicochemical quality analysis while total coliform, faecal coliform and total heterotrophic bacterial counts were determined for microbiological quality analysis. All the samples conformed to the WHO standards of TDS, salinity and conductivity. Except for 20% of the tap water samples, pH of all the samples was found to be satisfactory. The heterotrophic plate count was in a range of 8.0 x 101 cfu/ml to 9.3 x 105 cfu/ml from tap water sample and 6.5 x 101 cfu/ml to TNTC from dispenser water samples. Only 10% of the tap water samples and 30% of the dispenser water samples complied with the WHO stipulated limit of total heterotrophic count (100 cfu/ml). In terms of total coliforms, all the tap water samples and 20% of the dispenser water samples were found to be contaminated, whereas 50% of both the tap water and dispenser water samples were contaminated with faecal coliforms, indicating possible faecal contamination and presence of pathogenic bacteria. By comparing coliform/faecal coliform count on tap and dispenser water it was found that dispenser water is safer than tap water. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 69-72